Effect of Fiber Laser Parameters on Laser Welded AZ31B Magnesium Alloys - Muhammad Naqiuddin, Mat Salleh; M., Ishak; F. R. M., Romlay (EDP Sciences, 2017)
Recently, the usage of Magnesium (Mg) alloys has been hugely applied in the industrial application such as in automotive, marine, and electronic due to its advantages of recyclability and lightweight. This alloys required low heat input to be weld since it is easily evaporated due to the Magnesium Oxide (MgO) at the surface and it also possesses lower melting point compared to steel. Laser welding is more convenient to weld Mg alloys due to its high power and lower heat input. AZ31B was selected since it has strong mechanical properties among others Mg alloys due to the major alloying elements; Aluminium (Al) and Zinc (Zn). Low power fiber laser machine with wavelength of 900 nm was used in this experiment. The intention of this work was to investigate the effect of low power fiber laser parameters and effect of shielding gas on weld penetration and microstructure. Another aim in this work was to produce the joint for this thin sheets metal. Penetration depth and microstructure evaluation were emphasized in the analysis section. Bead-on-Plate (BOP) and laser lap welding was conducted on AZ31B with thicknesses of 1.0mm and 0.6 mm for feasibility study using pulsed wave (PW) mode. Defocusing features was used in order to find better focal position, which has less occurrence of evaporation (underfill). The effect of different angle of irradiation was also investigated. Two types of shielding gases, Argon (Ar) and Nitrogen (N2) were used in order to study the effect of shielding gas. Lastly, the effect of pulsed energy on penetration types and depth of BOP welded samples was investigated. Focus point was found at focal length of 156 mm with 393.75 µm. For BOP experiment, higher pulsed energy used contributes to melt through defect. Meanwhile, Ns shielding gas proved to be better shielding gas in laser welding the AZ31B. Higher angle of irradiation could reduce the underfill defect. Fillet Lap joint of similar metal was successfully done where 2.0 J of pulsed energy reveals better weld joint compared to 2.4 J.